Analisis Pengaruh Work from Home, Digital Platform dan Aplikasi Rapat Online terhadap Produktivitas Kerja pada PT. Telkom Akses di Jakarta Barat - Dwi Hafifah Perdiyanti; Dewi Puspaningtyas Faeni (Penerbit Goodwood, 2021)
Purpose: This research aimed to analyze the impact of Work from Home, Digital Platform, and Online Meeting Applications on Work Productivity. This research aimed to observe the correlation of the three factors of exogenous variables towards work productivity. Research Methodology: Sampling in this study used Random Sampling Techniques by spreading questionnaires to PT Telkom Access - West Jakarta towards 100 people. It shows that the population of PT Telkom Access - West Jakarta are 984 people. The methodology used to collect data was with the distribution of questionnaires. The statistical test tool utilized was SmartPLS 3.0. Results: Based on the results, the study shows that Work from Home positively affects work productivity, the Digital Platform positively affects work productivity, and the Online Meeting Applications positively affects Work Productivity.